Women in science: a daughter's perspective. (3rd July 2021) - Sokolowski, H. Moriah
Abstract: In the first grade, in one of my first classes, my teacher read us a story about a scientist. To my utter shock, the scientist was a man. After the story, I asked the teacher, 'can men be scientists?' She looked at me, bewildered, and replied: 'of course, anyone can be a scientist.' It was not until later that my teacher learned that my mother is a scientist, and the only scientists I had ever met were women, like me.